TRANSFORMATIONAL LEADERSHIP IN THE BRITTLE, ANXIOUS, NON-LINEAR AND INCOMPREHENSIBLE (BANI) ERA AFFECTING TEACHER TEAMWORK PERFORMANCE IN SCHOOLS UNDER CHANTHABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Bumbudtuk, Nareerut; Nilkote, Reongwit; Boonloy, Waiwoot (Journal of MCU Nakhondhat, 2024)
The purposes of this research were to: 1) Study the level of transformational leadership in schools under Chanthaburi Primary Educational Area Office 2 in the brittle, anxious, non-linear and incomprehensible (BANI) era, 2) Study the level of teamwork performance of teachers in these schools, 3) Determine the relationship between transformational leadership in the BANI era and teamwork performance of teachers in these schools, and 4) Create a predictive equation for the transformational leadership in the BANI era affecting teacher teamwork performance in these schools. It is quantitative research. The instrument used in the study was a questionnaire with a sample of 285 people. The sample size was determined using Krejcie and Morgan's table, and stratified sampling by proportion was used, with districts as the strata. The statistics used for data analysis included: mean, standard deviation, Pearson's correlation coefficient, and multiple regression analysis. The research results found that: 1) Opinions about transformational leadership in the BANI era were at the high level ( = 4.46, S.D. = 0.46); 2) Opinions about teamwork performance of teachers were at the high level ( = 4.44, S.D. = 0.39); 3) There was a moderately positive correlation between transformational leadership in the BANI era and teamwork performance of teachers, which was statistically significant at the 0.01 level; and 4) Transformational leadership in the BANI era had a significantly positive effect on teamwork performance of teachers at the 0.05 level. The multiple correlation coefficient was 0.574, and the predictive power accounted for 32.90% of the teamwork performance of teachers. The forecast equation in raw score format was: = 2.333 + 0.253 (X3) + 0.205 (X4), and the forecast equation in the form of a standardized score was: = 0.331 (X3) + 0.262 (X4). The study results align with the objectives and hypotheses set.